Hanji: Surviving Through the Ages. - Eun-kyung, Jeon (Koreana)
The article explores how Hanji, a traditional Korean paper made from mulberry bark, is gaining renewed global interest for its durability and moisture-regulating properties, making it valuable for cultural heritage restoration and contemporary art. Topics include traditional paper making, cultural heritage restoration; and contemporary art materials.